Brand Image and Experiential Marketing Drive Customer Loyalty in Mobile Coffee - Jenny Amelia Gifani; Indah Respati Kusumasari (Academia Open, 2025)
General Background: Coffee has evolved from a mere beverage into a cultural lifestyle symbol, particularly among Indonesia’s urban youth, fueling the rapid growth of mobile coffee businesses. Specific Background: URBN Contemporary Mobile Coffee in Surabaya exemplifies this shift, operating in a competitive market where brand image, pricing, and experiential strategies are vital for sustaining customer loyalty. Knowledge Gap: Despite extensive research on brand loyalty in traditional coffee shops, limited empirical evidence addresses how these factors influence loyalty within mobile coffee enterprises. Aims: This study aims to analyze the effects of brand image, price, and experiential marketing on brand loyalty among URBN Mobile Coffee consumers in Surabaya. Results: Using a quantitative associative design with 100 respondents, multiple linear regression revealed that brand image and experiential marketing significantly enhance brand loyalty, while price has a positive but insignificant effect; collectively, these variables explain 51% of loyalty variance. Novelty: This research extends brand loyalty theory to the mobile coffee sector by highlighting the dominance of intangible elements—perception and experience—over price. Implications: The findings suggest that cultivating a strong brand image and creating memorable customer experiences are more effective strategies for fostering sustainable loyalty in highly competitive coffee markets. Highlights:  Brand image and experiential marketing significantly strengthen customer loyalty. Price plays a minor role compared to perception and experience. Strong branding and memorable experiences ensure long-term loyalty. Keywords: Brand Image, Price, Experiential Marketing, Brand Loyalty, Mobile Coffee